Hemolysis interference in the determination of 25 biochemical constituents using ADVIA 1800 autoanalyzer - Saldaña O., Italo Moisés (2015)
Introduction. Hemolysis interference is the main cause of pre analytical rejection of serum samples in clinical laboratory. Objectives. To identify and quantify possible hemolysis interferences in the routine measurement of 25 biochemical constituents using ADVIA 1800 autoanalyzer, by clinical relevant interference criterion when the maximum desirable systematic error is exceeded. Design. Comparative descriptive study. Institution. Hospital Edgardo Rebagliati Martins, EsSalud, Lima, Peru. Biologic material. Blood samples collected from volunteer subjects. Interventions. Increasing amounts of hemoglobin (0.26 g/L, 0.53 g/L, 1.05 g/L, 2.10 g/L, 3.25 g/L, 4.30 g/L, and 5.25 g/L) were added to seven different aliquots of sera mixture and influence of interfering influence in 25 constituents was determined by duplicate. The Spanish Society of Clinical Chemistry protocol was followed. Main outcome measure. Hemolysisrelated relative percentage deviation of the constituent concentration compared with the sample without interference. Results. Urea, creatinine, uric acid, total bilirubin, HDL cholesterol, LDL cholesterol, triglycerides, calcium, and gamma glutamyl transferase showed no interference. Interference was observed for glucose, protein, albumin, cholesterol, potassium, phosphorus, magnesium, lactic dehydrogenase, creatine phosphokinase, aspartate aminotransferase, alanine aminotransferase, lipase, sodium, chlorine, alkaline phosphatase and amylase. Conclusions. Out of 25 constituentss studied, 16 had clinical significant interference. It is recommended that each laboratory investigate this interference effects using their own methods, reagents or instruments.